HUBUNGAN KEBIASAAN SARAPAN DENGAN KONSENTRASI BELAJAR SISWA KELAS TINGGI SDN 106 TOAWO KECAMATAN LILIRILAU KABUPATEN SOPPENG - Muliadi, Muliadi; Sudarto, Sudarto; Sel, Selvi (Bajang Institute, 2024)
This research is a correlational study which aims to determine whether there is or not a correlation between the breakfast habits and the learning concentration of the high grade students at SDN 106 Toawo, Lilirilau District, Soppeng Regency. The population in this study was all of the high grade school students, while the sample was the entire population, namely 42 students. The sampling technique used was a saturated sampling technique. Research data was obtained using an instrument in the form of a questionnaire with a Likert scale. The data analysis technique used was inferential statistical analysis. Research results: Pearson Product Moment correlation coefficient = 0.657 (strong category), rcount = 0.657, rtable = 0.304; rcount > rtable then H0 was rejected and H1 was accepted. Conclusion: there is a strong and significant correlation between the breakfast habits and the learning concentration of the high grade students at SDN 106 Toawo, Lilirilau District, Soppeng Regency